Investigation of Salivary RANKL and OPG Levels in Periodontitis Patients at Hospital Universiti Sains Malaysia - Asif, Saba; Ahmad, Basaruddin; Hamza, Syed Ameer; Taib, Haslina; Kassim, Nur Karyatee; Zainuddin, Siti Lailatul Akmar (European Journal of Dentistry, 2021)
Objective This study was aimed to determine the levels of salivary receptor activator of NF-κB ligand (RANKL) and osteoprotegerin (OPG) and its association with periodontal status among periodontitis patients.Materials and Methods A cross-sectional study was designed and performed at the Dental Clinic, Hospital Universiti Sains Malaysia (HUSM). Random sampling was employed to identify 88 participants into three groups: 30 mild periodontitis, 30 moderate to severe periodontitis, and 28 healthy (nonperiodontitis) patients. Periodontal parameters: periodontal pocket depth (PPD), clinical attachment level (CAL), plaque score (PS), and gingival bleeding index (GBI) were recorded. In total, 4 mL of unstimulated whole saliva was collected to determine the levels of salivary RANKL and OPG proteins by using ELISA technique. Data were analyzed by using SPSS software version 24.0.Results Mean values for PPD (5.3 ± 0.5) and CAL (5.6 ± 0.5) were observed higher for moderate to severe periodontitis as compared with values (4.4 ± 0.2) (4.5 ± 0.2) in mild periodontitis patients. The mean salivary RANKL and OPG was 0.23 ± 0.07 ng/mL and 1.78 ± 0.70 ng/mL respectively in moderate to severe periodontitis. Only salivary RANKL levels were significantly and positively correlated with all the clinical periodontal parameters.Conclusion The levels of salivary RANKL were higher as opposed to lower OPG levels in periodontitis patients in contrast to healthy (nonperiodontitis) patients. RANKL levels were significantly associated with the periodontal parameters. Therefore, we can conclude that RANKL can potentially aid as an adjunctive diagnostic protein in evaluating periodontal disease.
Keywords: periodontitis; receptor activator of NF-ĸB ligand; osteoprotegerin; Saliva